Effect of delay time on emission intensity spectral line Al (396,152 nm) stimulated by double-pulse laser - Trịnh Ngọc Hoàng; Nguyễn Bá Đương; Quách Văn Phục (Journal of Technical Education Science, 2015)
In this paper, the effect of time delay between two pulses of a double-pulse laser on the emission spectrum intensity of spectral line of Al I (396,152 nm) in the aluminum alloy D16 samples was investigated. The aluminum alloy D16 samples were bombarded in the air by using doublepulse laser Nd: YAG operating at wavelength of 1064 nm with different time delay periods. Based on the measured spectral data, graphs showing the dependence of emission spectrum intensity of spectral line of Al I (396,152 nm) onto the time delay of double-pulse laser excitation source were formed and analyzed.